Entrepreneurship During the COVID-19 Pandemic: A Systematic Literature Review and Future Research Agenda - Sufyan, Muhammad; Aleem, Majid; Ameer, Irfan; Mustak, Mekhail (Senate Hall, 2021)
Since the COVID-19 pandemic began, a growing body of literature has emerged that examines different aspects of entrepreneurship. It warrants the need for a systematic review to provide an overview of published research. Accordingly, the current study aims to examine how entrepreneurship research has addressed the COVID-19 pandemic. We achieve this objective by conducting a systematic review of 69 peer-reviewed articles published in 2020 and the first half of 2021. The findings have mainly identified four distinguishable themes: impact of the pandemic on entrepreneurial activities, responses of entrepreneurial firms toward the pandemic, resources and capabilities that facilitate such responses, and effects of government interventions on entrepreneurial activities. Moreover, our results indicate that the majority of research lacks explicit theoretical and methodological foundations, spans a broad range of industries, and is disproportionately concentrated in a few geographic regions. Lastly, our review proposes a comprehensive research agenda for the future of entrepreneurship in the context of the pandemic.
Keywords: COVID-19|crisis|entrpreneurship|opportunities